Предмет: Алгебра,
автор: MadMan14
Запишите многочлен (b-2) * (4b-5) - 4b * (b-2) в стандартном виде, должено быть решение а не только ответ, помогите...
Ответы
Автор ответа:
0
(b-2)*(4b-5)-4b*(b-2)=4b²-5b-8b+10-4b²+8b=-5b+10
Автор ответа:
0
(b - 2) * (4b - 5) - 4b * (b - 2) = (b - 2) * (4b - 5 - 4b) = -5(b - 2) =
= -5b -5 * (-2) = -5b + 10
= -5b -5 * (-2) = -5b + 10
Похожие вопросы
Предмет: Українська мова,
автор: bazhan2020
Предмет: Математика,
автор: yemetssasha41
Предмет: Математика,
автор: Xamil15
Предмет: Алгебра,
автор: Аноним